2022-RA-1298-ESGO Hormonal replacement therapy after gynecological malignancies – critical literature review. (20th October 2022) - Jansa, Vid; Skuk, Eva; Cvjeticanin, Branko; Suster, Natasa Kenda; Staric, Kristina Drusany; Kunic, Tina; Macek, Katja Jakopic; Lasic, Mateja; Kovac, Luka; Blaganje, Mija; Stefanovska, Marina Jakomovska; Kobal, Borut; et al.
Abstract : Introduction/Background: Hormone Replacement therapy (HRT) after surgery for gynecological malignancy is controversial. Although the first aim is achieving the best oncological outcome, we must take into consideration quality of life and long-term health outcomes. Most gynecological malignancies are considered hormonal dependent and therefore theoretically there is a risk that HRT increases the risk for recurrence of malignant disease. Methodology: A comprehensive literature research of studies on hormone replacement therapy in gynecologic cancer survivors was performed in the Pubmed Database for the literature published in the last 10 years. Results: HRT is contraindicated in survivors of breast cancer, endometrioid type of epithelial ovarian cancer, granulosa cell ovarian tumors, endometrial cancer, leiomyosarcoma and endometrial stromal sarcoma of the uterus. HRT is generally considered safe in epithelial ovarian cancer, vulvar, vaginal and cervical cancer. Caution is needed with adenocarcinoma of the cervix. Some studies seem to support that HRT does not impact negatively on outcome even in endometrial cancer survivors. Conclusion: HRT does not appear to increase the risk for gynecological malignant disease recurrence. Decision for HRT prescribing should be individualised and after patients informed consent.The gynecological-oncological society should encourage more studies and consider about concensus on HRT in cancer survivors to help gynecologist in every day practice and patients whith their everday menopausal issues.